Performance Analysis Of A Domestic Refrigerator - Mohd Yusof, Taib; Azizuddin, Abd Aziz (2010)
Refrigerator is one of the home appliance utilizing mechanical vapour compression cycle in it process. Performance of the system becomes main issue and many researches are still ongoing to evaluate and improve efficiency of the system. Therefore, this paper presents the development process of refrigerator test rig and performance analysis of a domestic refrigerator. The experiment platform which called test rig was developed from refrigerator model NRB33TA National brand. The main objective in this study was to obtain performance of the refrigeration system in term of Refrigeration Capacity, Compressor work and Coefficient of Performance (COP) by determining three important parameters during in operating mode which are temperature, pressure and refrigerant flowrate. In the test rig, all temperature probes were connected to thermocouple scanner to measure temperature at particular points on the refrigeration system. Pressure gauges were used to measure pressure and a magnetic flowmeter was used to measure refrigerant flowrate. In order to avoid effects of a changing the measured data, the environmental of testing was controlled according to Association of Home Appliance Manufacturers (AHAM) standard. There are three sets of experiment data were collected in order to evaluate the refrigerator performance. Each data was collected for a cycle of operation for 2 hours. The result shows that the average COP of the refrigeration system using the refrigerator test rig was about 2.7.